Hydro geochemical data on oil field water statistic validation - Aldana, Gerardo; Chourio, Ana; Zambrano, Orlando (Rev. Téc. Fac. Ing. Univ. Zulia, 2015)
Â Hydrogeochemical diagrams, such as Stiff diagrams, had been used to follow the finger print left by the cations and anions of the chemical elements present in produced water. To know the water source, it is necessary to perform a detailed analysis that includes the study of characterization and classification. The aim of this study was to analyze the data from the statistical point of view, to validate the certainty of the finger print and the composition of the chemical structure of water. In addition, water is used as an enhanced oil recovery method in order to optimize its production injecting into reservoirs. The methodology used consisted of the classification and analysis of 34 initial data of patterns of water from historical records, through the technique of the hydrogeochemistry analyzed in the laboratory from formation water. 20 samples were collected during the year 2012 in the wells from 5 reservoirs. The samples were taken from wellhead of each wells.Â The results indicated the progress of water front that was also confirmed by well completion logs. Uniform and normal distributions predominated in the fields and it was observed that Na + and Cl - ions increased their concentrations in the past 35 years in 2 log after the injection, which was validated through a variance of Pearson and Kolmagorov-Smirnov test. The relationship Na + vs. Cl - can be used as a tracer element injection in oil wells